Constructing Representations to Learn in Science
VIII, 210 p.
Keywords: Constructing Representations to Learn in Science Current research into student learning in science has shifted attention from the traditional cognitivist perspectives of conceptual change to socio-cultural and semiotic perspectives that characterize learning in terms of induction into disciplinary literacy practices. This book builds on recent interest in the role of representations in learning to argue for a pedagogical practice based on students actively generating and exploring representations. The book describes a sustained inquiry in which the authors worked with primary and secondary teachers of science, on key topics identified as problematic in the research literature. Data from classroom video, teacher interviews and student artifacts were used to develop and validate a set of pedagogical principles and explore student learning and teacher change issues. The authors argue the theoretical and practical case for a representational focus. The pedagogical approach is illustrated and explored in terms of the role of representation to support quality student learning in science. Separate chapters address the implications of this perspective and practice for structuring sequences around different concepts, reasoning and inquiry in science, models and model based reasoning, the nature of concepts and learning, teacher change, and assessment. The authors argue that this representational focus leads to significantly enhanced student learning, and has the effect of offering new and productive perspectives and approaches for a number of contemporary strands of thinking in science education including conceptual change, inquiry, scientific literacy, and a focus on the epistemic nature of science.